1995
DOI: 10.1016/s0022-5347(01)66738-7
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Unilateral Adrenal Hemorrhage: Computerized Tomography and Magnetic Resonance Imaging Findings in 8 Cases

Abstract: One must not consider the diagnosis of spontaneous adrenal hematoma only as superimposed on a phechromocytoma or malignant lesion in the case of an incidentally discovered large adrenal mass with normal biological findings. MRI signs of adrenal hemorrhage and the failure of enhancement of such a mass should strongly suggest adrenal hematoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 15 publications
1
46
1
3
Order By: Relevance
“…Although Moore and Biggs 6 initially reported a case of AH manifesting as an asymptomatic adrenal mass, their case could now be categorized as "incidentaloma". Hoeffel et al 4 also summarized eight cases of AH as "spontaneous" mainly for radiological imaging. However, four of these involved an asymptomatic mass and should therefore be redefined as incidentaloma, as in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Moore and Biggs 6 initially reported a case of AH manifesting as an asymptomatic adrenal mass, their case could now be categorized as "incidentaloma". Hoeffel et al 4 also summarized eight cases of AH as "spontaneous" mainly for radiological imaging. However, four of these involved an asymptomatic mass and should therefore be redefined as incidentaloma, as in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,5,8 Usamentiage et al 5 reported a case of spontaneous left adrenal gland rupture, and CT proved to be an accurate imaging modality, which helped to diagnose AH. Friedrichs et al 7 also reported a case of spontaneous right AH diagnosed by CT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, follow-up imaging studies are extremely important because hemorrhagic lesions in adenomas are not rare as in the present cases [13]. If the rapid enlargement of tumors with heterogeneous density occurs, surgery should be considered because of the possibility of malignancy and/or intratumor hemorrhage.…”
Section: Activities O F P450smentioning
confidence: 75%
“…However, at a subacute or a chronic stage CT findings of adrenal hemorrhage are variable and we are not able to distinguish it from other tumors. Hoeffel et al [7] reported that the findings of no enhancement or enhancement only in the pattern of a thin peripheral rim was noted in adrenal hemorrhage, but they were not specific to it. In this case, the adrenal mass was shown to have not only a peripheral rim but also a heterogeneous internal architecture with enhancement and seemed to be malignant.…”
Section: Discussionmentioning
confidence: 99%